Training Load, Well-Being, and Readiness Reducing Injury Risk and Improving Sports Performance - Clemente, Filipe Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The reprint represents the publication of the seven articles associated with the special issue "Training Load, Well-Being, and Readiness: Reducing Injury Risk and Improving Sports Performance". Within the reprint the readers can found evidence about training load monitoring in soccer, cyclists and regular gym exercises. We hope readers can find interesting the methodological approaches provided.